On Guanidinium and Cellular Uptake - Wexselblatt, Ezequiel (American Chemical Society, 2014)
[Image: see text] Guanidinium-rich scaffolds facilitate cellular translocation and delivery of bioactive cargos through biological barriers. Although impressive uptake has been demonstrated for nonoligomeric and nonpept(o)idic guanidinylated scaffolds in cell cultures and animal models, the fundamental understanding of these processes is lacking. Charge pairing and hydrogen bonding with cell surface counterparts have been proposed, but their exact role remains putative. The impact of the number and spatial relationships of the guanidinium groups on delivery and organelle/organ localization is yet to be established.